The protection of resveratrol and its combination with glibenclamide, but not berberine on the diabetic hearts against reperfusion-induced arrhythmias: the role of myocardial KATP channel. (15th March 2019) - Kaya, Salih T.; Bozdogan, Omer; Ozarslan, Talat O.; Taskin, Eylem; Eksioglu, Didem; Erim, Firdevs; Firat, Tulin; Yasar, Selcuk
Abstract: Context: Cardiovascular dysfunctions such as life-threatening arrhythmias are one of the main reasons of mortality and morbidity in diabetic patients Objective: We aimed to investigate the long-term effects of resveratrol, berberine and glibenclamide combinations on the ischemia/reperfusion (I/R) induced arrhythmias in streptozotocin (STZ)-induced diabetic rats and to investigate the role of myocardial KATP channel in the possible anti-arrhythmic actions of the treatments. Methods: Two days after induction of diabetes, diabetic rats were treated with resveratrol [5 mg/kg, intraperitoneally (i.p.)], berberine (10 mg/kg, i.p) and glibenclamide (5 mg/kg, i.p) for 6 weeks. On the 43th day, experimental animals were subjected to 6-min ischemia and 6-min reperfusion in vivo . Results: The protein expression of Kir6.2 subunits was downregulated in the diabetic hearts. However, all drug treatments restored the protein expression of Kir6.2 subunits. Resveratrol alone and its combination with glibenclamide decreased the arrhythmia score, the arrhythmic period and the incidence of other types of arrhythmias during the reperfusion period. Conclusions: The combination of resveratrol with glibenclamide may alleviate reperfusion-induced arrhythmias via an underlying mechanism not be only associated with the restoration of the protein expression of Kir6.2 subunits but also associated with the other subunits or ion channels underlying cardiac action potential.